Genome-wide association mapping identifies novel SNPs for root nodulation and agronomic traits in chickpea - Chandana, B. S.; Mahto, Rohit Kumar; Singh, Rajesh Kumar; Bhandari, Aditi; Tandon, Gitanjali; Singh, K. K.; Kushwah, Sunita; Lavanya, Gera Roopa; Iquebal, Mir Asif; Jain, Neelu; Kudapa, Himabindu; Upadhyaya, H. D.; et al. (Frontiers in Plant Science, 2024)
The chickpea (Cicer arietinum L.) is well-known for having climate resilience and atmospheric nitrogen fixation ability. Global demand for nitrogenous fertilizer is predicted to increase by 1.4% annually and the loss of billions of dollars in farm profit has drawn attention to the need for alternative sources of nitrogen. The ability of chickpea to obtain sufficient nitrogen via its symbiotic relationship with Mesorhizozbium ciceri is of critical importance in determining the growth and production of chickpea. In order to support findings on nodule formation in chickpea and to map the genomic regions for nodulation, we evaluated an association panel consisting of 271 genotypes, selected from the global chickpea germplasm including 4 checks (BG 372, BG 3022, BG 547 and BG 1105) selected from theglobal chickpea germplasmat four locations (IARI, New Delhi; SHUATS, Naini, Prayagraj, UP; KVK Vaishali campus, RPCAU, Samastipur, Bihar and IARI regional station, Pusa, Bihar)and data was recorded for nodulation and yield related twelve traits.namely;days to 50 % flowering, plant height, number of pods per plant, number of seeds per plant, yield per plant, number of nodules per plant, nodules per plant, nodule fresh weight, root fresh weight, root dry weight, stem fresh weight, and stem dry weight.The Genome wide Wide Association Study (GWAS) was conducted using phenotypic data and genotypic data extracted e marker datafrom whole genome resequencing data of chickpea , withby creating a hap map file consisting of 602344 SNPs in the working set was used as a genotypic datawith best fit 2 models of association mapping. The GWAS panel was found to be structured with sufficient diversity among the linesgenotypes. Linkage disequilibrium (LD) analysis has shown LD decay value of 37.3 MB indicating SNPs within this distance to behave as inheritance block. A total of 450 and 632 stringent marker trait associations (MTAs) were identified from the BLINK and FarmCPU models, respectively, for all the traits under studyand among them,. The 75 novel MTAs identified for nodulation traits were found to be stableand all the identified nodulation traits MTAs were novel.